Pengembangan Model Pengaruh Penggunaan Internet Terhadap Prestasi Akademik Mahasiswa Ranah Kognitif - Desi Pibriana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
The development of internet that increasing rapidly today, has encouraged almost all levels of education to provide internet facilities for the students especially in universities. Internet facilities should be used by the students in order to enrich their knowledge, learning process and helping them in doing paper, therefore it could help students to have a good academic achievement on campus. Several previous studies claimed that internet usage factor that associated by students’ academic achievement directly and others claimed that Academic SelfEfficacy can be a mediator between internet usage factor and students’ academic achievement. Therefore, using the method of literature study, this study was developed to generate a new model which includes about the factor that affect internet usage such as the ability to use, internet using motive, purpose dan function, information retrieval and time usage of internet which in further associated by the Academic Self- Efficacy and students’ academic achievemnet on cognitive factor either directly or indirectly. Academic Self- Efficacy factor are expected to strengthen the correlation between internet usage factor and students’ academic performance on cognitive domain, in this case can be measured by Cumulative Performance Index (CPI). Based on the results of the study, can be developed a new research that focuses either on the calculation of how much the internet usage can influence the student academic achievement on cognitive domain or more on other domain such as affective and psychomotor.